Assessment of adolescent self-constructed material use in physical education - Fernández-Río, Javier; Méndez-Giménez, Antonio; Méndez-Alonso, David (FEADEF, 2012)
the goals of this research project were three: study how secondary education students value self-made materials, assess their effects while used to teach sport, and analyze how the students' perspective on these materials change over age and gender. Students from a high school in the north part of Spain agreed to participate. They belonged to 1st, 2nd, and 4th year of secondary education. They were asked to build their own self-made cardboard ringo with recycled materials to use it during an ultimate learning unit. A hybrid instructional method (tactical games + sport education) was used along 8-10 sessions. After the intervention, subjects filled out a 15-item questionnaire (1-5 likert point scale). Overall results showed that subjects did not consider that building the ringo was hard. Finding the material was not difficult, either. They also thought that using the ringo was more fun than using the traditional Frisbee. Younger students valued the experience higher than older subjects. The usage of self-made materials was more attractive, motivating and useful for 1st year subjects. They also though that this type of material had helped them improve their throwing and catching skills. They even wanted to use it in extracurricular settings